2010
DOI: 10.1213/ane.0b013e3181cde713
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Causes Greater QTc Interval Prolongation in Elderly Patients than in Younger Patients

Abstract: Sevoflurane causes greater QTc interval prolongation in elderly patients than in younger patients. Although sevoflurane does not affect the transmural dispersion of repolarization and sevoflurane-induced QTc prolongation does not advance with time and by droperidol administration, QT interval prolongation and its associated arrhythmias should be carefully monitored during sevoflurane anesthesia in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
1
33
0
2
Order By: Relevance
“…However, these clinical studies targeted small numbers of patients and did not include those under general anesthesia. General anesthesia is a risk factor for QT interval prolongation because of the use of QT‐prolonging drugs or possible bradycardia in patients with preexisting comorbidities or electrolyte imbalances . Different from the first generation 5‐HT 3 receptor antagonists that are recommended for use at the end of surgery, palonosetron is recommended for use at anesthesia induction because of a slower onset of action .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, these clinical studies targeted small numbers of patients and did not include those under general anesthesia. General anesthesia is a risk factor for QT interval prolongation because of the use of QT‐prolonging drugs or possible bradycardia in patients with preexisting comorbidities or electrolyte imbalances . Different from the first generation 5‐HT 3 receptor antagonists that are recommended for use at the end of surgery, palonosetron is recommended for use at anesthesia induction because of a slower onset of action .…”
mentioning
confidence: 99%
“…General anesthesia is a risk factor for QT interval prolongation because of the use of QT-prolonging drugs or possible bradycardia in patients with preexisting comorbidities or electrolyte imbalances. [14][15][16] Different from the first generation 5-HT 3 receptor antagonists that are recommended for use at the end of surgery, palonosetron is recommended for use at anesthesia induction because of a slower onset of action. 17 Furthermore, to our knowledge, there have been no studies regarding the effects of palonosetron on perioperative cardiovascular complications in large numbers of patients under general anesthesia in real clinical practice.…”
mentioning
confidence: 99%
“…Class IA and III antiarrhythmic agents should be avoided because of a potential to prolong QTc [37][38][39] . Many of the anesthetic agents prolong QTc (inhaled anesthetics, droperidol, ondansetron, and succinylcholine) and should be administered with care [40][41][42][43] . Prolongation of the QT interval, intraventricular conduction disturbances, heart block, and ventricular bigeminy can occur with propoxyphene.…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…5,6 There is a strong correlation between QTc prolongation and the risk for torsade de pointes, but there is no absolute QTc threshold above which torsade de pointes routinely occurs. Several drugs that are routinely administered in the perioperative setting, such as antibiotics, sevoflurane, 710 or ondansetron 1113 have been shown to cause QTc interval prolongation. Furthermore, in a recent study we found that the 80% of patients undergoing noncardiac surgery under general anesthesia developed postoperative QTc prolongation with a median increase of 23ms.…”
Section: Introductionmentioning
confidence: 99%